2011
DOI: 10.12659/msm.881808
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blinded, placebo-controlled pilot study of probiotics in active rheumatoid arthritis

Abstract: SummaryBackgroundTo examine the effect of probiotics as adjunctive therapy for the treatment of rheumatoid arthritis (RA). A sample size of 30 subjects was calculated to determine a moderate effect.Material/MethodsA three month double-blind, placebo-controlled study was performed using probiotic Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 capsules administered orally. Inclusion criteria required at least 4 swollen and 4 tender joints and stable medications with no steroids for at least 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…[7][8][9][10][11][12] Therefore, it has been attempted to alleviate the symptoms of the disease through normalizing the gut bacterial pattern of the patients; administering probiotic preparations is one possible way to achieve this goal. [13][14][15] Animal studies have shown that various strains of Lactobacillus casei (L. casei) can efficiently decrease inflammatory cytokines in RA. [16][17][18][19] However, it is unclear whether this species can be efficacious for RA patients; the optimum dosage of this probiotic for presenting the consumer with the desired effects has not been determined either.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Therefore, it has been attempted to alleviate the symptoms of the disease through normalizing the gut bacterial pattern of the patients; administering probiotic preparations is one possible way to achieve this goal. [13][14][15] Animal studies have shown that various strains of Lactobacillus casei (L. casei) can efficiently decrease inflammatory cytokines in RA. [16][17][18][19] However, it is unclear whether this species can be efficacious for RA patients; the optimum dosage of this probiotic for presenting the consumer with the desired effects has not been determined either.…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant improvement in the Health Assessment Questionnaire score in the probiotic group. Although researchers did not detect clinical improvement, measured by the American College of Rheumatology criteria, authors reported functional improvement within the probiotic supplementation group compared with the placebo [63].…”
Section: Probiotic Applications In Ra Patientsmentioning
confidence: 94%
“…Some performed studies evaluating the effect of probiotics as an adjuvant therapy for RA treatment have shown no significant results, and some of these conducted studies have smaller number of patients and a short period of evaluation [63,64].…”
Section: Probiotic Applications In Ra Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Наоборот, применение в раннем возрасте пробиотиков, содержащих лактобациллы и/или бифидобактерии, снижает вероятность развития аллергических заболеваний [20]. Многие аутоиммунные заболевания ассоциированы с дисбиозом ТК [21], тогда как прием пробиотиков уменьшает выраженность клинических проявлений ревматоидного артрита [22]. Раскрытие молекулярных механизмов патогенеза болезни Крона, при которой генетический дефект передачи противовоспалительных сигналов от компонентов бактериальных клеточных стенок-мурамилпептидов-через NOD2-рецепторы приводит к развитию тяжелого воспалительного заболевания кишечника, также в значительной степени поддерживает тезис о толерогенной функции симбионтных бактерий [23].…”
unclassified